ADOPTION AND IMPACTS OF NATURAL RESOURCE CONSERVATION IN ARSI ZONE, ETHIOPIA - Challa, Tamrat Gebiso (International Journal of Research -GRANTHAALAYAH, 2021)
Land degradation in Ethiopia alone accounts for 8% of the global total degradation. The most serious problem concerning country’s land resources, however, is the removal of fertile topsoil by water. Population pressure which results to intensive cultivation, overgrazing deforestation and inappropriate land use practices are the most serious cause of soil erosion in Ethiopia which is more severe in the highlands areas where, 85% of the human and 77% of livestock population are living and agriculture is intensive. To reverse the situation the government of Ethiopia designed policy and programs which are holistic and landscape wide approaches. Based on the strategies, different soil and water management programs have been implemented throughout the country and different practices were introduced to farmers as well for more than ten years. The central questions of this research were, whether farmers adopt these soil and water conservation practices; and if yes, do these soil and water conservation interventions have an impact in improving crop production in value per hectare and gross annual income of participating households? If yes, how much is the impact? Based on above objectives, the research was conducted in Arsi zone and data was collected from 202 respondents in representative districts. Both adopters and counterfactual respondents were included. Educational background of households, farming experiences, size of landholding, slop of plot, degree of vulnerability of the districts and extension contact significantly and positively affect adoption probability while land fragmentation was significant and negatively influencing adoption of soil and water conservation (SWC) activity. Though it was not statistically significant, SWC adoption has positive impact on productivity, gross production and income of the household. The average treatment effect on treated (ATT) was 6358.86 ETB of total household income which could be proxy for farm level productivity and 85.35 quintal of total annual farm production.